From the Metabolic Effects and Mechanism of Monovalent Cation Transport to the Actual Measurement of the Plasma Membrane Potential in Yeast - Antonio Peña; Norma Silvia Sánchez; Martha Calahorra (Journal of Fungi, 2025)
The effects of potassium (K+) on yeast metabolism were documented as early as 1940. Studies proposing a mechanism for its transport started in 1950, and in 1953, a mechanism for the stimulation of fermentation was suggested. However, it was not until the 1970s that both mechanisms were clarified in Mexico, and the actual internal pH of the cells was measured. The presence of an H+-ATPase that generates an electric plasma membrane difference (PMP), which is used by specific transporters to facilitate the influx of K+ and other cations into the cells, was discovered. For years, many efforts were made to estimate and measure the value of the PMP; the obtained results were variable and erratic. In the 1980s, a methodology was developed to estimate the plasma membrane potential by following the fluorescence changes in the DiSC3(3) dye and measuring its accumulation, which provided actual but inaccurate values. Similar values were obtained by measuring the accumulation of tetraphenylphosphonium. The most reliable method of measuring the actual values of the plasma membrane potential was only recently devised using the also fluorescent dye thioflavin T. This review presents the attempts and outcomes of these experiments necessary to clarify the results reported by different research groups. Innovative research with Genetically Encoded Voltage Indicators (GEVIs) is also included.